Meningkatkan Keterampilan Proses Sains melalui Penerapan Metode Eksperimen pada Anak Kelompok B di TK Dharma Wanita Manding - Jayidah Al Islam (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
This study aims to improve children's science process skills through experimental methods in children in Group B of the Dharma Wanita Kindergarten, Manding Village. This research is a Classroom Action Research. The research model was carried out in two cycles, and each cycle was carried out in two meetings. The subjects of this study were 25 children in group B, comprising 15 boys and 10 girls. Methods of data collection are done through observation and documentation. The results showed that the experimental method could improve children's science process skills. No seven children (28%) had sufficient and good science process skills before the action were taken. After the action in Cycle I, children's science process skills increased by 13 children (52%), and in Cycle II increased to 19 children (76%) with moderate, good, and very good. In learning using the experimental method, the teacher invites children to discuss procedures, equipment, and materials for experiments as well as things that need to be observed during the experiment, then provide an explanation accompanied by examples. Furthermore, children can try to practice themselves, make observations, prove the truth of the predictions, overcome problems arising in the experiment, and draw conclusions.